Proceedings Commitee (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2024)
PROCEEDINGS OF THE SUNAN AMPEL INTERNATIONAL CONFERENCE OF POLITICAL AND SOCIAL SCIENCES (SAICOPSS) 2024 Editors Ajeng Widya Prakasita, M.A. Dr. H. Moh Syaeful Bahar, M.Si Dr. Dwi Setianingsih, M.Ag. Dr. Moh. Ilyas Rolis, M.Si. Firmansyah, M.Ag. Masitah Effendi, MSi Reviewers Dr. Zudan Rosyidi, M.A. Zaky Ismail, M.S.I. Dr. Iva Yulianti Umdatul Izzah, M.Si. Dr. Amal Taufiq, M.Si. Wahyu Ilahi, M.A. Dr. Abid Rohman, S.Ag., M.Pd.I. Moh Fathoni Hakim, M.Si. Dr. Hj. Aniek Nurhayati, M.Si. Laili Bariroh, M.Si. Dr. Akhmad Siddiq, M.A. Nur Luthfi Hidayatullah, S.IP., M.Hub.Int. Prof. Dr. Abd. Chalik, M.Ag. Wahidah Zein Br Siregar, Ph.D. Noor Rohman, M.A. Speakers Dr. Abdul Muein Bin Abadi (Universiti Kebangsaan Malaysia) Dr. Ali Kassem (National University of Singapore) Prof. Cyril Hovorun (University College Stockholm) Dra. Hj. Wahidah Zein Br Siregar, MA., Ph.D. (UIN Sunan Ampel Surabaya)